Daclatasvir/Sofosbuvir versus Ledipasvir/Sofosbuvir in Patients with Hepatitis C Virus Infection Genotypes 1 and 3 - Shokatpour, Narjes; Sali, Shahnaz; Khahanipour, Ali; Abolghasemi, Sara; Shabani, Minoosh (Novelty in Biomedicine, 2020)
Background: The new direct-acting antiviral agents (DAAs) with high efficacy, low resistance, and low rate of adverse events (AEs) have shown promising outcomes for hepatitis C virus (HCV) treatment. This study assessed the efficacy and safety of Daclatasvir/Sofosbuvir (DCV/SOF) compared to Ledipasvir/Sofosbuvir (LDV/SOF) in patients with HCV infection in the real-world setting in Iran. Materials and Methods: A total of 42 patients with HCV infection were treated with either LDV/SOF (genotype 1) or DCV/SOF (genotypes 1, 3 or unknown) with or without ribavirin (RBV). Assessment of risk factors, laboratory tests, sustained virologic response at post-treatment week 12 (SVR12), and AEs were performed. Results: The highest risk factor for HCV transmission was major surgery (50.0%), followed by tattooing (40.5%), phlebotomy (40.5%), and dental surgery (40.5%). No statistically significant relationships between genotypes and risk factors were observed. In both treatment groups (LDV/SOF and DCV/SOF), all of the patients (100%) with or without cirrhosis and treatment-experience achieved SVR12. One patient with a history of failed LDV/SOF therapy achieved SVR12 following retreatment with DCV/SOF. Both treatment regimens were well-tolerated. No serious AEs or discontinuation due to AEs was observed. The most common AE across both treatment groups were fatigue (42.9%), followed by anxiety (28.6%). Numerically, more adverse events were found with the LDV/SOF regimen than with the DCV/SOF regimen. Conclusion: Our study showed an excellent safety and efficacy of DCV/SOF and LDV/SOF in Iranian patients infected with HCV. The incidence of AEs among patients treated with LDV/SOF was higher than those receiving SOF/DCV.